Pemberdayaan Masyarakat Sekolah melalui Penguatan Literasi Digital Berbasis AI dan AR dalam Eksplorasi Sains di SMAN 4 Barru : Penelitian - Surianto, Dewi Fatmarani; Zulfikar, Muh Ihsan; Hasnining, Ayu; Agusyana, Nurrahmah; Nirmala, Putri; Awalia, Andi Dio Nurul (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The development of digital technology requires teachers to have adequate digital literacy in order to be able to design innovative, relevant, and adaptive learning that meets the needs of students. This activity aims to improve the competence of teachers at SMAN 4 Barru in utilizing AI Chatbot (LioraTa'), ChatGPT, and Augmented Reality (AR) for biology learning. The implementation method was carried out through Participatory Action Research (PAR) involving 26 teachers and students from SMAN 4 Barru. Evaluation was conducted through pre-tests and post-tests as well as direct observation of practice. The first result showed an increase in the average score from 8.896 (74%) on the pre-test to 10.733 (89%) on the post-test, indicating a significant improvement in teachers' understanding of digital literacy. The second result was that teachers acquired practical skills in designing chatbot conversation flows, compiling ChatGPT-based teaching materials, and utilizing AR for biology experiments, making learning more interactive and contextual. The third result was that teachers reported an increase in confidence in using digital technology and awareness of the importance of AI and AR-based learning innovations to support the quality of education. In conclusion, this training successfully had a positive impact on teachers' mastery of concepts, practical skills, and readiness to integrate digital technology into biology learning, while also strengthening their position.